In memoriam: Ljupčo Melovski - Hristovski, Slavčo; Jovanovska, Daniela (Macedonian Journal of Ecology and Environment, 2019)
Ljupčo Melovski was born on 30.6.1958 in Gostivar. He spent his childhood in Galičnik village and in 1964 he moved to Skopje. He completed his secondary education in the SixthForm College Rade Jovčevski Korčagin in Skopje. He enrolled in the studies at the Biological Faculty in Skopje in 1977 and graduated in 1981 with a BSc thesis on systematics of higher plants: Distribution of the Species of Families Boraginaceae and Lamiaeceae on Bistra Mountain. He took employment at the Biological Faculty, Division of Botany, Department of Plant Ecology in 1984, and since the beginning he was engaged in the scientific and educational activities of the Faculty. He was promoted to young lecturing assistant in 1984 and reelected in 1990. In 1992 he was promoted to the position of a teaching assistant and reelected in 1995. He was promoted to assistant professor in 1997, associated professor in 2002 and full time professor in 2007. From the early beginnings of his scientific career he was involved in the scientific project Complex Ecosystem Research of the Macedonian Oak Ecosystem Quercetum frainetto-cerris in Galičica National Park. The collected data served as foundation for both his master’s thesis Dynamics of Forest Floor, Annual Litter Production, Decomposition Rate and Soil CO2 Release in the Italian and Turkey oak Forest Ecosystem in Galičica National Park, defended in 1991, and his doctoral dissertation - Nutrient Cycling in the Macedonian Quercetum frainettocerris Ecosystem in Galičica National Park. He also took part in excess of 15 other scientific and research projects and he was responsible for coordination of three of them. During his scholarly career, he visited numerous research centers and attended professional training in ecosystem and environmental research in Spain, Germany, England and the USA. He was coordinator of the Division of Botany with Botanical Garden in two mandates in the period 2005-2009. Prof. Ljupčo Melovski was part of an array of applicative projects, especially in the sphere of biodiversity and nature protection. He was part of the expert team that drafted the Law on Nature Protection, and he made significant contribution in drafting the national strategies on biodiversity and nature along with scores of expert studies and strategic documents in the domain of environmental protection in different parts of Macedonia and in South-Eastern European countries. He was a member of the Macedonian Ecological Society (MES) since 1984. He was President of MES in the period 2001-2014.